Drinking water assessment on ammonia exposure through tap water in Kampung Sungai Sekamat, Kajang - Rashid, Nur Shafarina; Sarva Mangala Praveena,; Aris, Ahmad Zaharin (Elsevier, 2015)
The study was intended to analyze ammonia and physicochemical characteristics (pH, temperature, conductivity, total dissolved solid and turbidity) in tap water in Kampung Sungai Sekamat, Kajang. This study was also to estimate the chronic daily intake (CDI) of ammonia exposure through tap water. A total number of 106 water samples were collected in Kampung Sungai Sekamat residents were involved in this study. Tap water analysis results showed that the mean concentration of ammonia was 0.03 mg/L ± 0.19 mg/L. Ammonia and physicochemical characteristics were below Malaysian Standard Drinking Water Quality (MSDWQ) except for pH and turbidity. A low positive significant correlation was observed between total dissolved solids and ammonia. Mean chronic daily intake (CDI) was 0.0007 mg/day/kg ± 0.004 mg/day/kg and below than provisional tolerable weekly intake